Elephant-poaching weapons and new experiences from the Banyang-Mbo Wildlife Sanctuary, Cameroon - Nchanji, Anthony (Pachyderm, 2005)
Article reviews a decade long Wildlife Conservation Society’s antipoaching campaign in Banyang-Mbo Wildlife Sanctuary in southwestern Cameroon. A map showing where the elephant carcasses werer found and the villages wherein poaching equipment was found links this activity to ethnic groups living in different areas in the vicinity. 183 elephants were known to have been illegally killed or poached between January 1993 and January 2004. The present population is estimated to be 214 +/-159. The animals were mostly poached for their ivory, the meat was generally consumed fairly quickly. However, lately the carcasses are often simply left to rot. Firearms using locally made bullets are often used. Both rifles and shotguns have been confiscated by the antipoaching programme. Snares made of cable wire and pin-board traps which pierce the elephants’ footpads are common. Notes that crop raiding is present and agriculturalists are antagonistic towards elephatns. Antipoaching campaigns should assess this aspect and make conflict mitigation part of any programme.